Selective Oxidation and Carbonization by Laser Writing into Porous Silicon. Issue 1 (21st October 2018) - Keating, Adrian; Sun, Xiao
Abstract: The selective formation of either oxidized or carbonized features into 2.5 µm thick porous silicon (PS) films using laser writing at a wavelength of 405 nm is demonstrated. Oxidized features are formed in air while carbonized features are achieved during the flow of propane at 600 sccm. Voids which have been previously associated with the use of propane are not observed, largely due to the rapid heating and high flow rates achieved in the experiment. Carbonized regions with feature widths down to 1.8 µm are achieved and chemical resistance to both hydrofluoric acid and potassium hydroxide is demonstrated. Once carbonized regions are formed, the surrounding areas can be overwritten in air to convert the surrounding regions into oxidized PS allowing films to be created with as‐fabricated, oxidized and carbonized regions. Energy dispersive X‐ray and Raman analysis confirms the presence of carbon within the written structures. At high optical powers, cracking around the carbonized features is observed which is attributed to a contraction of the film. Such cracking is not observed during selective oxidation of features. This work significantly enhances the ability to engineer and pattern the composition of PS films enabling selective control of the material's properties and functionality. Abstract : A laser written carbonized porous silicon pattern of the University of Western Australia crest . In Step #1, a laser beam passivates the porous film under C3 H8 flow. In Step #2 a wider laser beam oxidizes the film in air. Scanning electron microscope and energy‐dispersive X‐ray (EDX) spectroscopy measurements taken after hydrofluoric acid immersion to remove the oxide.